Do consumers from Međimurje region recognize their autochthonous Turoš cheese? - Kristijan Valkaj; Marija Cerjak; Samir Kalit; Ante Rako; William L. Wendorff (Mljekarstvo)
The aim of this study was to determine whether consumers from the Međimurje region recognise and distinguish the autochthonous cheese called Turoš from similar cheeses like Prgica and Kvargl originating from regions neighbouring to Međimurje. Chemical, textural and microbiological properties of all three cheeses were given. Preference tests with 200 consumers using a face-to-face survey and a two-step procedure were performed. The blind taste test showed that 97 % of the respondents recognised differences between the tasted samples, and almost half of them preferred the Turoš cheese. Similarly, the informed test showed that a significantly higher number of the respondents preferred the Turoš cheese in comparison to Kvargl and Prgica. Statistical analyses showed no significant differences between respondents’ preferences in the blind and the informed tests.